INNOVATIONS IN CUSTOMER EXPERIENCE: ENHANCING ENGAGEMENT AND LOYALTY - Iskandarov Sunnatillo Baxriddin o‘g‘li; Qobuljonov Shoxboz Shukrullo oʻg‘li; Sadinov Davronbek Komil oʻg’li (Web of Journals Publishing, 2024)
In today's competitive business landscape, providing exceptional customer experiences has become essential for organizations to drive engagement and foster customer loyalty. This article explores innovations in customer experience (CX) strategies aimed at enhancing engagement and loyalty. It examines emerging trends and technologies shaping the CX landscape, such as artificial intelligence (AI), machine learning, data analytics, and personalized marketing. Additionally, it delves into the importance of omni-channel customer engagement, proactive customer service, and community-building initiatives in building lasting relationships with customers. By embracing innovative CX approaches, organizations can differentiate themselves in the marketplace, drive customer satisfaction, and cultivate long-term loyalty.
Keywords: customer experience, cx innovations, engagement, loyalty, artificial intelligence, machine learning, data analytics, personalization, omni-channel, proactive customer service.